Prognostic Significance of Modified Residual Disease in Breast and Nodes (mRDBN) Algorithm After Neoadjuvant Chemotherapy for Breast Cancer. Issue 4 (22nd February 2018) - Clark, Beth Z; Farrugia, Daniel J; Landmann, Alessandra; Diego, Emilia J; Dabbs, David J; Puhalla, Shannon L; Jankowitz, Rachel C; Brufsky, Adam M; Ahrendt, Gretchen M; McAuliffe, Priscilla F; Bhargava, Rohit
Abstract: Objectives: We hypothesized that prognostic accuracy of the residual disease in breast and lymph nodes (RDBN) method, which is calculated using residual tumor size, nodal involvement, and tumor grade, may be improved by incorporating residual tumor cellularity. Methods: Cases included 614 patients who underwent neoadjuvant therapy for breast cancer. Tumor size was adjusted for residual cellularity of invasive carcinoma and used to calculate modified RDBN (mRDBN) and compared with unmodified gross tumor size (gRDBN). Results: RDBN could be calculated in 428 cases. Relative risks of recurrence and death were significantly higher for RDBN-3 and RDBN-4 compared with RDBN-1. Kaplan-Meier analysis showed significant differences in disease-free survival and overall survival for estrogen receptor (ER)-negative/human epidermal growth factor receptor 2 (HER2)-negative and ER-positive/HER2-negative subgroups (P < .0001). Conclusions: Both mRDBN and gRDBN provide prognostic information, particularly in HER2-negative carcinoma; however, mRDBN showed better stratification of RDBN-3 and RDBN-4 patients.